Immunoprotective Activity Induced by Leptospiral Outer Membrane Proteins in Hamster Model of Acute Leptospirosis - Teixeira, Aline F.; Cavenague, Maria F.; Kochi, Leandro T.; Fernandes, Luis G.; Souza, Gisele O.; de Souza Filho, Antonio Francisco; Vasconcellos, Silvio A.; Heinemann, Marcos Bryan; Nascimento, Ana L. T. O. (Frontiers in Immunology, 2020)
Leptospirosis is a zoonotic disease of worldwide distribution, affecting both humans and animals. The development of an effective vaccine against leptospirosis has long been pursued but without success. Humans are contaminated after direct contact with the urine of infected animals or indirectly by contaminated water or soil. The vaccines available consist of inactivated whole-bacterial cells, and the active immunoprotective antigen is the lipopolysaccharide moiety, which is also the basis for serovar classification. However, these vaccines are short-lasting, and protection is only against serovars contained in the preparation. The search for prevalent antigens, present in pathogenic species of Leptospira, represents the most cost-effective strategy for prevention of leptospirosis. Thus, the identification of these antigens is a priority. In this study, we examined the immunoprotective effect of eight leptospiral recombinant proteins using hamster as the challenge model. Animals received subcutaneously 2 doses of vaccine containing 50 μg of each recombinant protein adsorbed on alum adjuvant. Two weeks after the booster, animals were challenged with virulent leptospires and monitored for 21 days. All proteins were able to induce a specific immune response, although significant protective effects on survival rate were observed only for the proteins Lsa14, rLIC13259 and rLIC11711. Of these, only rLIC13259 and rLIC11711 were found to be highly prospective in promoting renal clearance. The sterilizing potential of both proteins will be further investigated to elucidate the immunoprotective mechanisms involved in leptospirosis control. These are the first proteins involved with human complement components with the capacity to protect against virulent challenge and to eliminate the bacteria from the host.